2021
DOI: 10.1103/physrevb.104.144402
|View full text |Cite
|
Sign up to set email alerts
|

Weak three-dimensional coupling of Heisenberg quantum spin chains in SrCuTe2O6

Abstract: The magnetic Hamiltonian of the Heisenberg quantum antiferromagnet SrCuTe 2 O 6 is studied by inelastic neutron scattering technique on powder and single-crystalline samples above and below the magnetic transition temperatures at 8 and 2 K. The high-temperature spectra reveal a characteristic diffuse scattering corresponding to a multispinon continuum, confirming the dominant quantum spin chain behavior due to the third neighbor interaction J intra = 4.22 meV (49 K). The low-temperature spectra exhibit sharper… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 26 publications
1
7
0
Order By: Relevance
“…4(b) depicts the T -dependent C m at zero field, which is manifested by the presence of a broad maximum centered at about 14 K. This broad maximum is believed to arise due to the presence of short-range spin correlations, indicating toward the low D magnetism and has been reported in various S = ½ as well as S = 1 chain compounds. 15–18,39,40,42 Generally, this kind of broad maximum in C m is a signature of short-range magnetic interactions among the spins and is found to exist at a relatively lower temperature than the broad maximum observed in magnetic susceptibility. Another notable feature is that the C m remains almost zero up to a finite temperature (∼4 K) before showing a rapid increase at higher temperatures.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…4(b) depicts the T -dependent C m at zero field, which is manifested by the presence of a broad maximum centered at about 14 K. This broad maximum is believed to arise due to the presence of short-range spin correlations, indicating toward the low D magnetism and has been reported in various S = ½ as well as S = 1 chain compounds. 15–18,39,40,42 Generally, this kind of broad maximum in C m is a signature of short-range magnetic interactions among the spins and is found to exist at a relatively lower temperature than the broad maximum observed in magnetic susceptibility. Another notable feature is that the C m remains almost zero up to a finite temperature (∼4 K) before showing a rapid increase at higher temperatures.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, the series ACuTe 2 O 6 (A = Pb, Ba, Sr) has gained a lot of interest in the context of QSL state and low D magnetism. 7,8,15–18 The magnetic properties in this series do not only depend on the 1 st near neighbor (NN) but also on the next NN interactions. In particular, the Pb-based member exhibits field induced QSL state due to the dominance of a highly-frustrated Hyperkagome network formed by the 1 st and 2 nd NN magnetic interactions.…”
Section: Introductionmentioning
confidence: 87%
“…In case the frustration is lowered allowing magnetic order to occur, the expected ordered moment will be very small as the spectral weight of the excitations is lowered below ∼0.4 meV at lower temperature [8]. When compared to the simulated diffraction magnetic Bragg peak and the energy scale of the spin waves in the isostructural unfrustrated compound SrCuTe 2 O 6 which develops long-range magnetic order (1.25 meV ) [33,34], the ordered moment in PCTO can be estimated to be less than 0.1µ B . It should however be noted that the magnetic measurement of C.Thurn et.al [15] do not find an accompanying magnetic transition, rather suggesting that the highly frustrated state survives in the single crystal below the transition with enhanced quantum critical behavior compared to the powders.…”
Section: Discussionmentioning
confidence: 98%
“…The interchain interactions were also investigated by inelastic neutron scattering. By fitting the lowenergy magnetic spectrum at low temperatures to spin-wave theory, Chillal et al [17] showed that the FM J 2 /AFM J 6 model is compatible with the data while an AFM J 1 also explains the spectrum.…”
Section: Introductionmentioning
confidence: 96%
“…Evidence for this comes from broad peaks due to short-range order in the DC susceptibility and heat capacity [12][13][14][15][16]. Furthermore, inelastic neutron scattering finds that the excitations form a spinon continuum characteristic of the spin-1/2 Heisenberg antiferromagnetic chain [17]. Physical properties measurements also reveal two transitions to long-range magnetic order and a complex phase diagram as a function of magnetic field and temperature [12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%